EFEKTIVITAS METODE BERNYANYI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS ANAK KELOMPOK B - Iftaturrohmah; Nanik Yuliati; Suhartiningsih (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This research was conducted in group B TK Dharma Wanita Tembokrejo Muncar Banyuwangi. The background of this research is because there are still many children who are confused and cannot clearly show the English that has been spoken by the teacher so it is necessary to optimize the mastery of English vocabulary by using audiovisual media in the form of video. This study aims to determine whether the use of audiovisual media is effective or not on the mastery of English vocabulary in group B. The type of research used is a quasi-experimental design with a Non-Equivalent Control Group. The sample in this study were group B children with a total sample of 24 respondents. Methods of data collection using tests, observations with check lists and documentation. The results obtained from the results of the pretest and posttest in the experimental and control groups before and after the treatment there were significant differences. The results of the difference between the pretest and posttest in the experimental group were 34.89, the control group was 25, so that tcount = 2,778 and t table with db = 22 at a significance level of 5%. The value of tcount is greater than ttable (2,778>2,074), it shows that there is a difference in vocabulary mastery between children who are treated using audiovisual media and children who are not treated using audiovisual media.